The Inactivation of Plasma Thromboplastin by Heparin - Cross, M. J; Glover, Susan (Thrombosis and Haemostasis, 1963)
Heparin at concentrations greater than 0.2 u/ml rapidly inactivated partially purified thromboplastin (plasma prothrombinase) prepared from pigs’ plasma in the thromboplastin generation test.